Deliberative Governance dalam Fromulasi Kebijakan Perlindungan Buruh di Banyumas - Tasroh, Tasroh; Setyoko, Paulus Israwan (Jurnal Administrasi Publik, 2024)
The labor protection agenda in the local government landscape faces many problems. Among others, the problem of low participation and consensus rates in the Employment Social Security as mandated by Law Number 13 of 2003 concerning Manpower, Law Number 2 of 2023 concerning Job Creation and Law Number 40 of 2004 concerning the National Social Security System. This study aims to explore and find models of labor protection policy deliberations at the regional level as an integral part of labor protection policies. With a case study in Banyumas Regency and through a descriptive-qualitative data approach and analysis supported by in-depth observations and interviews with a number of policy makers at the regional level, it can be concluded that there are 2 ideal deliberative governance models for labor protection policy formulation that can be applied to accelerate the achievement of labor protection policy performance. Namely it is the core actor deliberation model and the supporting actor deliberation model, all of which involve cross-actors and interests. Through dinamic cross-actor deliberation network, improvements in interaction patterns  and integrated communication flows have proven effective in increasing the roles, tasks and authorities of cross-actors to jointly formulate labor protection policies in accordance with the mandate of central government regulations. Participation and consensus can also be built more democratically, because all actors have autonomy and open and independent dialogue space so that the formulation of labor protection policies that include work accident protection, old age security, pension security, death security and job loss security runs dynamically and productively.